Meningkatkan Kemudahan Pembelajaran Digital Marketing Menggunakan Mobile Learning di SMAN 2 Aikmel - Widia Febriana; Rini Anggriani; I Nyoman Yoga Sumadewa; Melati Rosanensi (Target : Jurnal Manajemen Bisnis, 2023)
Technological developments are currently growing rapidly. The rapid development of technology affects the progress of a business marketing process. One of the technological developments in the marketing process is digital marketing. Digital marketing is an attempt to promote a product using internet media with the aim of winning the competition to attract consumers and potential customers efficiently. There are many ways that must be learned to carry out digital marketing so that digital marketing can be carried out efficiently and does not harm a business owner who will carry out digital marketing. Little knowledge of digital marketing in general and little material and android applications that discuss digital marketing that can be accessed online or offline is one of the reasons for the lack of understanding of someone who will develop a learning process at SMAN 2 Aikmel. Researchers made an article with the title "improving the ease of learning digital marketing using mobile learning at SMAN 2 Aikmel with the aim that it can be used to study digital marketing materials and increase understanding of digital marketing learning in schools using mobile learning. The method used to make this article is the Gamma Feedback Learning Model (GFLM) method with the Computer Assisted Instruction (CAI) model stored in the Learning Management System (LMS). Based on the test results, it can be concluded that this research can help improve students' understanding according to the aspects that have been measured in this study.